2018
DOI: 10.1111/ffe.12863
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue performance of RC beams strengthened with CFRP under coupling action of temperatures and vehicle random loads

Abstract: Considering significant influence of servicing environments and vehicle random loads on fatigue performance of main load‐bearing members of bridges, in this paper, fatigue performance of reinforced concrete bridge structures strengthened with carbon fibre–reinforced polymer under coupling action of environmental temperatures and vehicle random loads was studied. A vehicle random loading spectrum for fatigue tests was simulated and compiled. A fatigue testing method with coupling action of random loads and temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Latin where M is the section flexural moment, f η is the internal arm coefficients of CFRP and it is suggested to take as 0.95 in Lin et al (2019).…”
Section: The Proposed Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Latin where M is the section flexural moment, f η is the internal arm coefficients of CFRP and it is suggested to take as 0.95 in Lin et al (2019).…”
Section: The Proposed Theoretical Modelmentioning
confidence: 99%
“…The basis of the durability design was proposed for the high strength concrete structures reinforced by CFRP. Several studies (Biosca et al, 2019;Ferrier and Agbossou, 2017;Lin et al, 2019;Lopez et al, 2003) focused on the flexural and fatigue properties of concrete beams strengthened with CFRP plates under temperature field. It can be concluded that the high temperature condition has an adverse effect on the bearing capacity of interfacial debonding.…”
Section: Introductionmentioning
confidence: 99%
“…Algorithms 2019, 12,260 3 of 14 plate. The sensor scan plane is parallel to the ground and perpendicular to the drive direction.…”
Section: Design Principle Of 3d Laser Scanning Systemmentioning
confidence: 99%
“…Certain damage, which have considerable impact on structure reliability and security, are inevitably retained because of the influence of fatigue load [10][11][12]. The process of causing damage caused by cyclic loading includes the combined results of the cumulative process of crack initiation, expansion and final fracture.…”
Section: Introductionmentioning
confidence: 99%
“…A reliability index was analyzed by considering the coupling effect of wet-dry action and load. Lin et al (2019) investigated the fatigue behavior of CFRP reinforced concrete bridge under the effect of both high temperature and vehicle loads. A fatigue testing method was proposed and the fatigue damage mechanism was analyzed as well.…”
Section: Introductionmentioning
confidence: 99%